Clinicians’ Perception and Management of Cancer Patients’ Decision Making Burden - Fiorella L. Huijgens; Inge Henselmans; Mette J. Huisinga; Gwen M. P. Diepenhorst; Hanneke W. M. van Laarhoven; Anke J. M. Oerlemans; Marij A. Hillen (Journal of General Internal Medicine, 2026)
Abstract Background Clinicians in cancer care are increasingly expected to involve patients in treatment decision making. Some patients may feel burdened by such involvement. It is unclear how clinicians recognize and respond to patient burden in shared decision making (SDM). Objective We aimed to gain more insight into experiences of oncology clinicians regarding patients’ burden of involvement in decision making. Design We used semi-structured in-depth qualitative interviews. Participants and Approach Clinicians who discussed curative treatment options with patients who had breast or prostate cancer were purposively sampled and interviewed. Questions addressed how clinicians detected, explained and addressed patient burden. Interviews were audio-recorded and transcribed verbatim. Analysis Two researchers inductively coded the interviews using thematic analysis. Key Results Clinicians ( N = 20) described several indicators of patient burden, such as the question “What would you do, doctor?”, patients assuming notably active or passive roles in decision making, and stalling or rushing the decision. Clinicians attributed patient burden to uncertainty, unmet expectations, and emotional vulnerability post-diagnosis. They indicated using various strategies to mitigate burden, such as normalizing the difficulty of decision making, or offering time to think. Clinicians varied in their willingness to provide a treatment recommendation. Some offered it to prevent potential burden due to uncertainty or decisional distress, while others refrained from giving explicit advice, believing that SDM entails patients should make their own choice. Conclusion Clinicians’ responses to perceived decision making burden in patients were variable. Discussions about how to navigate tensions between autonomy and avoiding harm could foster greater unity among clinicians on addressing patients’ burden in SDM.